Making Millennials Stay - Mirandha Ariesca Riana (SEIKO : Journal of Management & Business, 2021)
Millennials like job-hopping. This is a challenge for organizations given the high number of workers who are millennials. Organizations need to understand the characteristics of millennials and what they are looking for in a workplace to increase their commitment if they are to be a part of the organization. Sense of belonging is important to note because it can affect organizational commitment. The purpose of this study is to determine the effect of individual characteristics, organizational characteristics, job characteristics, and sense of belonging to organizational commitment. The population in this study were students of master of management in Makassar who are millennials and have worked or are currently working. The number of samples is determined by 100 respondents. Data were obtained through questionnaires then analyzed using path analysis. The results showed that individual characteristics positively and significantly affect organizational commitment but organizational and job characteristics do not. Individual and organizational characteristics have a positive and not significant effect on sense of belonging while job characteristics positively and significantly affecting sense of belonging. Sense of belonging positively and significantly affects organizational commitment and is an intervening variable that influences the relationship between individual, organizational, and job characteristics with organizational commitment. Keywords : Individual characteristics; job characteristics; millennials; organizational characteristics; organizational commitment; sense of belonging.